The F1Fo-ATP synthase α subunit of Candida albicans induces inflammatory responses by controlling amino acid catabolism - Shuixiu Li; Yuting Liu; Luobei Weng; Yajing Zhao; Yishan Zhang; Zhanpeng Zhang; Yang Yang; Qiaoxin Chen; Xiaocong Liu; Hong Zhang (Virulence)
Sepsis is a leading cause of fatality in invasive candidiasis. The magnitude of the inflammatory response is a determinant of sepsis outcomes, and inflammatory cytokine imbalances are central to the pathophysiological processes. We previously demonstrated that a Candida albicans F1Fo-ATP synthase α subunit deletion mutant was nonlethal to mice. Here, the potential effects of the F1Fo-ATP synthase α subunit on host inflammatory responses and the mechanism were studied. Compared with wild-type strain, the F1Fo-ATP synthase α subunit deletion mutant failed to induce inflammatory responses in Galleria mellonella and murine systemic candidiasis models and significantly decreased the mRNA levels of the proinflammatory cytokines IL-1β, IL-6 and increased those of the anti-inflammatory cytokine IL-4 in the kidney. During C. albicans-macrophage co-culture, the F1Fo-ATP synthase α subunit deletion mutant was trapped inside macrophages in yeast form, and its filamentation, a key factor in inducing inflammatory responses, was inhibited. In the macrophage-mimicking microenvironment, the F1Fo-ATP synthase α subunit deletion mutant blocked the cAMP/PKA pathway, the core filamentation-regulating pathway, because it failed to alkalinize environment by catabolizing amino acids, an important alternative carbon source inside macrophages. The mutant downregulated Put1 and Put2, two essential amino acid catabolic enzymes, possibly due to severely impaired oxidative phosphorylation. Our findings reveal that the C. albicans F1Fo-ATP synthase α subunit induces host inflammatory responses by controlling its own amino acid catabolism and it is significant to find drugs that inhibit F1Fo-ATP synthase α subunit activity to control the induction of host inflammatory responses.